PENGARUH SOSIOEMOSI DAN PERKEMBANGAN MORAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI SMA NEGERI DI KOTA PALU - Indah Suciati (MATEMATIKA DAN PEMBELAJARAN, 2016)
This research was made based on the internal and external factors which influenced the students’ learning outcomes. The study aimed at examining the profile and the influence of socio-emotion and moral development toward Mathematics learning outcomes of grade XI students of public senior high schools (SMAN) in Palu. This study was an ex-post facto causality study. The subject of the research was XI grade students of SMAN in Palu of academic year 2012/2013, selected by employing proportional stratified rendom sampling. The instruments of the study were scale method and test of Mathematics learning outcomes. Data were then analyzed through descriptive statistics and path analysis. The result revealed that (1) from 360 of grade XI students of SMAN in Palu have: self-concept with fair category, self-esteem with high category, moral development with high category, cognitive learning outcomes with low category, and affective learning outcomes (attitude towards Mathematics) with high category; (2) there was positive and significant correlation between self-concept and self-esteem; (3) there was positive and significant correlation between cognitive learning outcomes and affective learning outcomes; (4) self-concept gave influence directly to cognitive learning outcomes and gave indirect effect to moral development and affective learning outcomes; (5) self-esteem gave no direct effect to cognitive learning outcomes, but gave indirect effect to selfconcept, moral development, and affective learning outcomes; (6) self-concept gave influence directly to affective learning outcomes and gave indirect effect to moral development and cognitive learning outcomes; (7) self-esteem gave no direct effect to affective learning outcomes, but gave indirect effect to selfconcept, moral development, and cognitive learning outcomes. Key words: Self concept, self esteem, moral development, mathematics learning outcomes.